2016
DOI: 10.1177/0300060515624936
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of postoperative delirium in elderly hip fracture patients

Abstract: ObjectiveTo explore the risk factors associated with postoperative delirium (PD) in elderly patients following total hip arthroplasty (THA) for hip fracture.MethodsThis prospective study enrolled elderly patients (≥ 65 years) with hip fractures who underwent THA under general anaesthesia, and who had a complete set of postoperative observations. Detailed medical history and perioperative characteristics were recorded. During the postoperative period, patients were assessed twice daily for PD using the Confusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 45 publications
6
98
1
6
Order By: Relevance
“…A short delirium episode was defined as a postoperative delirium for 1 or 2 days. 12,[19][20][21][22][23][24] In agreement with most of these studies, we did not find an association between preoperative serum CRP levels and postoperative delirium in patients undergoing surgery for hip fracture. Duration of delirium was defined as the number of days with delirium according to CAM criteria.…”
Section: Assessment Of Delirium Severity and Durationsupporting
confidence: 91%
See 1 more Smart Citation
“…A short delirium episode was defined as a postoperative delirium for 1 or 2 days. 12,[19][20][21][22][23][24] In agreement with most of these studies, we did not find an association between preoperative serum CRP levels and postoperative delirium in patients undergoing surgery for hip fracture. Duration of delirium was defined as the number of days with delirium according to CAM criteria.…”
Section: Assessment Of Delirium Severity and Durationsupporting
confidence: 91%
“…7,9,10 Delirium has been associated with higher serum levels of the acute-phase protein C-reactive protein (CRP) in medical and surgical patients, [11][12][13][14][15] but neutral findings have been reported as well. 12,[19][20][21][22][23][24] Possible explanations for these discrepancies are small sample sizes, comorbidity, elective hip arthroplasty versus acute surgery for hip fracture, and differences in time points of blood sampling. However, studies in more homogenous patient groups, such as patients undergoing hip surgery, also have produced inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, procedures associated with longer operation times and more invasiveness, such as Cx and open radical nephrectomy, had high incidences of postoperative delirium. These operations are associated with multiple factors that could induce delirium, such as general anesthesia, mechanical ventilation, severe pain and intense inflammatory responses . The results suggest that the risk of postoperative delirium in urological surgery is clearly correlated to the invasiveness of the operation.…”
Section: Discussionmentioning
confidence: 97%
“…Many other studies have suggested preoperative cognitive impairment as a risk factor . A history of CVD is a well‐known risk factor for delirium . In addition, hypoalbuminemia is also a well‐known risk factor for dementia in hospitalized patients, including those undergoing surgery, in many studies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation